A Survey Research: What is the Role of the Mendeley Application in the Student Environment? - Simamora, Rumiris (Indonesian Journal of Education and Social Humanities, 2024)
The use of reference or citation managers such as Mendeley has begun to be applied by students in making scientific papers, especially making bibliography. This research aims to survey the role of the Mendeley application among students. This research is survey research. The sample for this research is final year students. Data was collected using a questionnaire technique which was accommodated with a Google form. The data obtained is quantitative data which is then analyzed using descriptive statistical techniques. From the sample of students who filled out the questionnaire, the results obtained were that some students knew and applied Mendeley, but others had difficulty and did not understand how to use Mendeley.